Materials for Writing – Was This the Case of the Runaway Bandwagon? - Nuraini, Kristi (ELLITE, 2017)
The teaching of language has developed from time to time. Writing as oneof the skills in language learning has also gone through different concerns;starting from less concerned in the Audio Lingual Method (ALM), becoming tohave more concerned in the Communicative Approach of Language Teaching(CALT). The materials also differ for the focus of language learning are different;from forms or structure focused into meaning or communicative focus; fromcontrolled activities into more natural and communicative ones. This paper will cover the teaching of writing, techniques of gathering ideas for writing and the influences of methodologies in writing tasks.